Effective Strategies for Human Resources Training and Development To Improve Employee Competence - Camelia Najwa; Della Dwi Lestari; Maharani Kusumaningtyas; Najla Asla Salsabilla (Takaza Innovatix Labs Ltd., 2026)
Human resource (HR) training and development is a key pillar of modern organizational management, aiming to build employee competency sustainably. This study comprehensively examines strategies proven effective in designing, implementing, and evaluating HR training and development programs in both government and private organizations in Indonesia. Using a systematic literature review approach to 20 scientific sources published between 2020 and 2025, the study identified that training program effectiveness depends not solely on the delivery method but also on the accuracy of the training needs analysis, the quality of the curriculum design, the consistency of implementation, and the relevance of the evaluation instruments used. The findings indicate that blended learning approaches, competency-based training, and the development of a culture of continuous learning are the three strategies that most consistently produce significant and measurable improvements in employee competency. The study also highlights several structural barriers that often hinder program success, including budget constraints, employee resistance to change, and weak post-training monitoring systems. As a practical contribution, this article formulates a model for integrated training strategies that can be adapted by various types of organizations according to their respective contexts and capacities. Policy implications and operational recommendations are included to support evidence-based decision-making in HR management.